Obtención de carburo de silicio mediante pirólisis a partir de relaves mineros de Portovelo. - Tapia Galarza, Eliana Milagros; Choez Tobo, Cristopher Manuel (My University, 2025)
The main objective was to develop a method to obtain SiC from tailings from the El Tablón community tailings dam, using petroleum coke as a reducing agent. The technical feasibility of the process was evaluated according to the temperature and reaction time, in addition to chemically and mineralogically characterizing the starting materials. Pyrolysis was used to obtain silicon carbide (SiC), applying high temperatures in an inert atmosphere together with petroleum coke. Sodium carbonate (Na₂CO₃) was incorporated as a flux to reduce the melting temperature and facilitate the formation of SiC, which improves the efficiency of the process compared to conventional methods of carbothermal reduction. An experimental design of 32 was performed with a single non-replicated central point. The analyses showed that the tailings contain 26.46% silicon, with quartz as the main phase (58.1%), along with pyrite (14.7%) and muscovite (17.2%). Coke showed a high proportion of amorphous carbon (70.5%) and lower amounts of sulfur and iron. These characteristics make both materials suitable for the proposed process. SiC was obtained under a factorial design 32, varying temperature (1100, 1200 and 1300 °C) and time (2, 4 and 6 hours). The results showed that SiC formation is significantly dependent on both variables. The ANOVA analysis and Tukey's test confirmed statistically significant differences between conditions such as 1100 °C/2h and 1300 °C/6h (p = 0.0000), while there were no relevant variations between 1100 °C/2h and 1100 °C/6h (p = 0.9361). At 1300 °C and 6 hours, the highest yield was obtained, with an average of 5.68 g SiC, equivalent to 2.58 % conversion compared to the initial mixture. In contrast, at 1100 °C and 6 hours, the conversion was only 0.13%. The response surface revealed a non-linear behavior, where temperature turned out to be the most influential factor and time acted as an enhancing variable. These findings validate the efficiency of the process and its potential to valorize mining waste through the synthesis of advanced materials.
El objetivo principal fue desarrollar un método para obtener SiC a partir de relaves de la relavera comunitaria El Tablón, empleando coque de petróleo como agente reductor. Se evaluó la viabilidad técnica del proceso en función de la temperatura y tiempo de reacción, además de caracterizar químicamente y mineralógicamente los materiales de partida. Se utilizó la pirólisis para obtener carburo de silicio (SiC), aplicando temperaturas elevadas en atmósfera inerte junto al coque de petróleo. Se incorporó carbonato de sodio (Na₂CO₃) como fundente para reducir la temperatura de fusión y facilitar la formación de SiC, lo que permite mejorar la eficiencia del proceso respecto a métodos convencionales de reducción carbotérmica. Se realizó un diseño experimental de 32 con un solo punto central no replicado. Los análisis mostraron que los relaves contienen 26,46 % de silicio, con cuarzo como fase principal (58,1 %), junto a pirita (14,7 %) y moscovita (17,2 %). El coque mostró una alta proporción de carbono amorfo (70,5 %) y cantidades menores de azufre e hierro. Estas características hacen que ambos materiales sean adecuados para el proceso propuesto. La obtención de SiC se realizó bajo un diseño factorial 32, variando temperatura (1100, 1200 y 1300 °C) y tiempo (2, 4 y 6 horas). Los resultados demostraron que la formación de SiC depende significativamente de ambas variables. El análisis ANOVA y la prueba de Tukey confirmaron diferencias estadísticamente significativas entre condiciones como 1100 °C/2h y 1300 °C/6h (p = 0,0000), mientras que no hubo variaciones relevantes entre 1100 °C/2h y 1100 °C/6h (p = 0,9361). A 1300 °C y 6 horas se obtuvo el mayor rendimiento, con una media de 5,68 g de SiC, equivalente al 2,58 % de conversión respecto a la mezcla inicial. En contraste, a 1100 °C y 6 horas, la conversión fue de apenas 0,13 %. La superficie de respuesta reveló un comportamiento no lineal, donde la temperatura resultó ser el factor más influyente y el tiempo actuó como variable potenciadora. Estos hallazgos validan la eficiencia del proceso y su potencial para valorizar residuos mineros mediante la síntesis de materiales avanzados.
Keywords: RELAVES MINEROS; PIROLISIS; TEMPERATURA; CARBURO DE SILICIO